Analysis of the Legal Challenges of Enacting Effective Communal Intellectual Property Data Collection System in Indonesia - Aicha Grade Rebecca (Syntax Corporation Indonesia, 2024)
This article discusses challenges arising from the implementation of the communal intellectual property registration system based on Regulation No. 13 of 2017 by the Minister of Law and Human Rights on Communal Intellectual Property Data. The urgency to conduct this research lies on the fact that Indonesian is rich in cultural heritage that acts as a basis for communal intellectual property but there are limitations in the existing communal intellectual property protection system. The purpose of this research aims to identify obstacles and challenges faced by relevant stakeholders in complying with the regulation. Research methods include normative legal research through secondary data that includes regulations, official documents, book reports and journals. The results reveal discrepancies between existing registration practices and the requirements stipulated in the regulation. Identified issues include negligence in data collection, a lack of understanding of the regulation, and resource limitations. The implications of these issues create barriers to the effectiveness of Communal Intellectual Property registration system.The article explores alternative solutions to enhance the performance of the registration system, including improvements in implementation guidelines, capacity-building for industry players, and strengthening collaboration among communal intellectual property stakeholders